2013
DOI: 10.5424/sjar/2013114-4093
|View full text |Cite
|
Sign up to set email alerts
|

Field analysis of the deterioration after some years of use of four insect-proof screens utilized in Mediterranean greenhouses

Abstract: The installation of insect-proof screens on greenhouse vents is one of the principal methods of protection against harmful insects for crops. Their main disadvantage lies on their negative effects on natural ventilation and greenhouse microclimate, which have been the focus of studies by several authors. However, few works have analysed the effect of accumulated dust and dirt on these screens. The present study has analysed four anti-insect screens, comparing their geometric characteristics before installation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The methodology used to characterise the geometry of the insect-proof screens was developed at the University of Almería [36,37,38]. For each insect-proof screen, three samples of approximately 2.04 cm 2 were analysed.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology used to characterise the geometry of the insect-proof screens was developed at the University of Almería [36,37,38]. For each insect-proof screen, three samples of approximately 2.04 cm 2 were analysed.…”
Section: Methodsmentioning
confidence: 99%
“…The above-mentioned negative aspects of the screens may be exacerbated by the accumulation of dust and dirt in the pores of the mesh (Linker et al, 2002;López et al, 2013). Over time the structure of the mesh deteriorates, and López et al (2013) observed that the thread diameter increases by an average of 3.1% and the porosity of the screen suffers a mean reduction of 6.5%.…”
mentioning
confidence: 99%
“…Over time the structure of the mesh deteriorates, and López et al (2013) observed that the thread diameter increases by an average of 3.1% and the porosity of the screen suffers a mean reduction of 6.5%. The accumulation of dust and dirt in the insect-proof screens gives rise to a mean reduction in the porosity of the insect-proof screens of 20.3%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, wind tunnels have emerged as a useful and cost-effective laboratory technique for the improvement of greenhouse structures [ 10 , 11 , 12 ], the study of climate control systems [ 13 , 14 , 15 , 16 ] and the estimation of the aerodynamic parameters of the experimental models. A number of applications of wind tunnels have been described in the literature on greenhouse engineering, including the determination of drag coefficients for horticultural crops [ 17 ], the study of aerodynamic parameters of insect-proof screens [ 2 , 18 , 19 , 20 , 21 , 22 ] and of greenhouse cooling systems [ 13 , 23 , 24 ], the assessment of wind erosion on agricultural soils [ 25 , 26 ] and the analysis of insect flight mechanisms [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%